Is it worth it? Postsecondary education and labor market outcomes for the disadvantaged - Ben Backes; Harry J. Holzer; Erin Velez (IZA Journal of Labor Policy, 2015)
In this paper we examine a range of postsecondary education and labor market outcomes, with a particular focus on minorities and/or disadvantaged workers. We use administrative data from the state of Florida, where postsecondary student records have been linked to UI earnings data and also to secondary education records. Our main findings can be summarized as follows: 1) Gaps in secondary school achievement can account for a large portion of the variation in postsecondary attainment and labor market outcomes between the disadvantaged and other students, but meaningful gaps also exist within achievement groups, and 2) Earnings of the disadvantaged are hurt by low completion rates in postsecondary programs, poor performance during college, and not choosing high-earning fields. In particular, significant labor market premia can be earned in a variety of more technical certificate and Associate (AA) programs, even for those with weak earlier academic performance, but instead many disadvantaged (and other) students choose general humanities programs at the AA (and even the BA level) with low completion rates and low compensation afterwards. A range of policies and practices might be used to improve student choices as well as their completion rates and earnings.
Keywords: I23; I24; J24; J31; 330; Disadvantaged; Postsecondary; Earnings; Achievement; Completion; Associate Degree; Bachelor's Degree